1984
DOI: 10.3109/01485018408987513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Migration and Capacitation on the Nuclear Stability of Human Sperm

Abstract: A possible change in the nuclear stability of the human spermatozoa further than ejaculation was investigated. A nuclear chromatin decondensation ability test using 1% SDS + 6 mM EDTA was used on spermatozoa migrated for 1 h in a swim-up migration (in BWW + human serum albumin 0.8%) and capacitated for 5 h in the same medium. The results, analyzed as paired series, showed that (1) capacitated and migrated spermatozoa have a greater nuclear stability than that of the control population (total sperm), (2) there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…We observed a significant increase in Feulgen-DNA content as well as in mean nuclear surface area both in B2 and in FF. Such results do not confirm earlier results concerning the effect of migration and capacitation on the nuclear stability of human sperm (Huret and Courtot, 1984). However, that study used a nuclear chromatin decondensation ability test that evaluated the induced swelling of the spermatozoa heads.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…We observed a significant increase in Feulgen-DNA content as well as in mean nuclear surface area both in B2 and in FF. Such results do not confirm earlier results concerning the effect of migration and capacitation on the nuclear stability of human sperm (Huret and Courtot, 1984). However, that study used a nuclear chromatin decondensation ability test that evaluated the induced swelling of the spermatozoa heads.…”
Section: Discussioncontrasting
confidence: 81%
“…Many studies have highlighted the condensationldecondensation process that affects mammalian spermatozoa chromatin either during the spermiogenesislsper-bility as suggested by a nuclear decondensation ability test (Huret and Courtot, 1984). This paper reports on two experiments designed to study the effects on human sperm chromatin of in vitro capacitation without decondensing agents.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been found that migration also selects a population with a better-stabilized nucleus [21]. It is therefore probable that a deficient spermiation and/or an incomplete maturation could allow an hypostabilization of the chromatin [21]. This hypothesis seems to be confirmed by the results obtained on a population of teratozoosperm [6].…”
Section: Optimal Stability Of the Nucleus And In Vivo Decondensationsupporting
confidence: 78%
“…It is known that in vitro swim-up migration selects sperm for good morphology and motility [36] and then eliminates most of the sperm having had a deficient spermiogenesis or an incomplete maturation in the epididymis. On the other hand, it has been found that migration also selects a population with a better-stabilized nucleus [21]. It is therefore probable that a deficient spermiation and/or an incomplete maturation could allow an hypostabilization of the chromatin [21].…”
Section: Optimal Stability Of the Nucleus And In Vivo Decondensationmentioning
confidence: 99%
See 1 more Smart Citation